Aerodynamic limits of gas turbine compressor during high air offtakes for minimum load extension. (5th May 2021) - Szymanski, Artur; Igie, Uyioghosa; Abudu, Kamal; Hamilton, Richard
Highlights: Minimum load extension with 18% of flow extraction from the back of the compressor. CFD show high flow separation and loss at the hub region of OGV at high extraction. Last stage of multi-stage compressor is the most affected by the aerodynamic limits. Use of 0D analytical engine model to enable high-fidelity 3D component computation. Abstract: Renewable energy sources (RES) have become a favoured alternative to fossil fuel energy generation that has been driven by environmental concerns. Their intermittent nature has meant that gas turbines have remained relevant to support them as a backup. Current grid operation requires gas turbines to operate at as low power as possible when their demand drops, and also ramp-up quickly when power generation from renewables declines. Air extraction from a gas turbine compressor can address the first requirement, as this mechanism reduces the load or power of the engine while storing the air for further pressurised reinjection, related to ramp-up rate improvements. This study demonstrates the aerodynamic implications and the limits to air extraction behind the last stage of the compressor, to achieve further minimum load reduction. To achieve this, a zero-dimensional (0D) analytical model of an engine at design and off-design conditions (air extraction) has been used to determine the boundary conditions for a 3D compressor Computational Fluid Dynamics (CFD) model. The multi-stage CFD model shows the aerodynamic implications of low to high air extractions that are limited by choke, high flow separation, and loss in the pressure at the hub region of OGV and last stage stator. As such, the back of the compressor was more affected than the earlier stages. Based on these, the limit of flow extraction is 18% (of the compressor discharge). The compressor of the analytical engine model showed similarity in trends for comparable conditions with the stand-alone 3D compressor, however, more optimistic than the latter. The work has shown that the compressor is capable of high airflow extractions to reduce the minimum load further.